Chemopreventive Effect of Statin on Hepatocellular Carcinoma in Patients With Nonalcoholic Steatohepatitis Cirrhosis. (2nd November 2021) - Pinyopornpanish, Kanokwan; Al-Yaman, Wael; Butler, Robert S.; Carey, William; McCullough, Arthur; Romero-Marrero, Carlos
Abstract : INTRODUCTION: To estimate the annual incidence of hepatocellular carcinoma (HCC) in patients with nonalcoholic steatohepatitis (NASH) with advanced liver fibrosis, to determine the risk factors for the development of HCC, and to evaluate the chemoprotective effect of statin use stratified by fibrosis stage. METHODS: We conducted a retrospective study at 2 US tertiary academic centers, including patients with NASH-related advanced liver fibrosis (bridging fibrosis [F3] and cirrhosis [F4]) followed between July 2002 and June 2016. Patients were followed from the date of diagnosis to the time of last abdominal imaging, liver transplantation, or HCC diagnosis. Multivariable Cox regression analysis was performed to evaluate the risk factors associated with HCC development, stratified by fibrosis stage. RESULTS: A total of 1, 072 patients were included: 122 patients with F3 fibrosis and 950 patients with cirrhosis. No HCC was observed during 602 person-year follow-up among F3 patients. Among patients with cirrhosis, HCC developed in 82 patients with the annual incidence rate of 1.90 per 100 person-years (95% confidence interval [CI], 1.53–2.35). Multivariable analysis in patients with cirrhosis demonstrated that HCC development was associated with male sex (hazard ratio [HR] 4.06, 95% CI, 2.54–6.51, P < 0.001), older age (HR, 1.05, 95% CI, 1.03–1.08, P < 0.001), and CTP score (HR, 1.38, 95% CI, 1.18–1.60, P < 0.001). Statin use was associated with a lower risk of developing HCC (HR, 0.40, 95% CI, 0.24–0.67, P = 0.001). Each 365 increment in cumulative defined daily dose of statin use reduced HCC risk by 23.6%. DISCUSSION: Our findings suggest that patients with NASH and bridging fibrosis have a low risk of HCC. Dose-dependent statin use reduced HCC risk significantly in patients with NASH cirrhosis.